PERANCANGAN SISTEM INFORMASI PEMINJAMAN BUS SEKOLAH DINAS PERHUBUNGAN UNIT PENGELOLA ANGKUTAN SEKOLAH DKI JAKARTA BERBASIS JAVA (Universitas Methodist Indonesia, 2022)
This study aims to create a borrowing system that is more effective and efficient than the borrowing system used in the previous DKI Jakarta School Transportation Management Unit. Makes data storage more secure than using paper media. Making reports easier and more accurate. The research method used in this research is the descriptive method, namely by collecting data through documentation, observation, and interviews. Where in making this application design is used with Unified Modeling Language (UML) Use Case, Sequence Diagram, Class Diagram design tools and use the Java programming language with Netbeans editor and MySQL database using XAMPP. The result of this study is that there is a rental application that can assist the borrowing process and also provide convenience for the DKI Jakarta School of Transportation Management Unit Transportation Service in managing borrower data, registration, loan data, and officer data stored in the database.